ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY, INTELLECTUAL CAPITAL, DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Setya Nurhudha, Adhita; Suwarti, Titiek (Proceeding SENDI_U, 2015)
This study examines the effect of corporate social responsibility and environmental performance of the companysfinancial performance. This research was conducted at the Indonesian Stock Exchange by using a go publicmanufacturing company as the unit of analysis. The sampling method used purposive sampling with the observationperiod from 2009 to 2013. Relationship and (or) influence between variable is described by using multipleregression analysis. The results showed that the corporate social responsibility and environmental performance haspositive effect and significant to the companys financial performance. Whereas intellectual capital does not effecton the companys financial performance.KeywordS : Corporate Social Responsibility, Intellectual Capital, Environmental Performance, and FinancialPerformance